2010 5th ACM/IEEE International Conference on Human-Robot Interaction (HRI) 2010
DOI: 10.1109/hri.2010.5453201
|View full text |Cite
|
Sign up to set email alerts
|

Can a robot deceive humans?

Abstract: In the present study, we investigated whether a robot is able to deceive a human by producing a behavior against him/her prediction. A feeling of being deceived by a robot would be a strong indicator that the human treat the robot as an intentional entity. We conducted a psychological experiment in which a subject played Darumasan ga Koronda, a Japanese children's game, with a robot. A main strategy to deceive a subject was to make his/her mind believe that the robot is stupid so as not to be able to move quic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…At its core, deception conveys intentionality [31], and that the robot has a theory of mind for the deceived [4] which it can use to manipulate their beliefs. It makes interactions with robots more engaging, particularly during game scenarios [28,31,32].…”
Section: Introductionmentioning
confidence: 99%
“…At its core, deception conveys intentionality [31], and that the robot has a theory of mind for the deceived [4] which it can use to manipulate their beliefs. It makes interactions with robots more engaging, particularly during game scenarios [28,31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Terada and Ito [13] demonstrated that a robot is able to deceive a human by producing a deceptive behavior contrary to the human subject's prediction. These results illustrated that an unexpected change of the robot's behavior gave rise to an impression in the human of being deceived by the robot.…”
Section: Previous Researchmentioning
confidence: 99%
“…After caching is complete, the robot then begins to move between the caching locations in order to patrol its resources. The behaviors of the robot include goal-oriented movement, selecting places, and waiting behavior as shown Taxonomy Definition Examples H-S-P Deceiving human for deceiver robot's own benefit using physical interactions Camouflage robots -DARPA's soft robot [1] N-S-P Deceiving other robot or nonhuman for deceiver robot's own benefit using physical interactions N/A H-O-P Deceiving human for deceived human's benefit using physical interactions Android Robots N-O-P Deceiving other robot or nonhuman for deceived other's benefit using physical interactions N/A H-S-B Deceiving humans for deceiver robot's own benefit using behavioral interactions Robot deception in HRI [13] N-S-B Deceiving other robots or nonhumans for deceiver robot's self benefit using behavioral interactions…”
Section: Robot Deception: a Case Studymentioning
confidence: 99%
“…Terada and Ito [16] demonstrated that a robot is able to deceive a human by producing a deceptive behavior contrary to the human subject's prediction. These results illustrated that an unexpected change of the robot's behavior gave rise to an impression in the human of being deceived by the robot.…”
Section: Robot Deceptionmentioning
confidence: 99%